Managing Normative Challenges and Deceptive Publishing: An Introspective Analysis of Social Science Research Practices - Prakash Upadhyay, Prakash (The Himalayan Geographers, 2025)
The civilizational advancement depends on research, and social science research is no exception to it since it helps in comprehending the complexities of the modern world, human and societal behaviour, critical thinking, testing theories, and evidence-based policy formation. Nevertheless, embedded with human experiences and societal advancement, normative or ethical norms are the standards of any social science research. This article points to major challenges in the field today: the normative intricacies in research where human participants are involved, like informed consent, privacy, and potential harm, and the upsurge of publishing predatory materials that threatens the integrity of academic work. The article comprises a literature review, historical case analysis, and content evaluation based on a qualitative methodology. It focuses on issues and gaps and advocates an applied and adaptable normative ethical guidelines that guide researchers in avoiding deceptive, pseudo-journals, and publications. Using frameworks developed by scholars such as Jeffrey Beall and Eriksson & Helgesson, the article sketches common features of predatory publishing and provides researchers with tools to assess the legitimacy of the journal. Finally, the article explains the close link between ethical research practices and trustworthy publishing. It argues that keeping ethical integrity and avoiding deceptive journals is essential for protecting participants and preserving public trust in social sciences academics. The findings suggest a practical, evidence-based guide for current and future researchers to write impactful, responsible, and trustworthy academic authorship.